ESSENCE AND COMPOSITION OF SOCIOECOLOGICAL AND ECONOMIC SAFETY OF FORESTRY ENTERPRISES (Economic journal of Lesya Ukrainka Volyn National University, 2018)
The article deals with approaches to the definition of social, ecological, economic and socioecological andeconomic security of the enterprise. On the basis of the generalization of the obtained results, the main features of socioecological andeconomic safety of forest enterprises are determined. The term safety has many meanings and is characteristic of any sphere of human activity. Today, scientists distinguish economic, ecological, demographic food, military, resource, energy, price, financial and monetary, political, social, criminal, medical, information, scientific and intellectual security.In the process of research, we found that socioecological and economic safety of forestry should be considered from the point of view of the systematic approach. Also, we have investigated which content content will have social, economic and environmental safety for the forestry sector. A feature of the forestry is that its activities are entirely based on the natural resources of the forest. It should be noted that the social security of the forestry is based on the principles of social responsibility of the business (observance of the current legislation and regulations, rules of felling, reproduction and improvement of forests, participation in social projects, cooperation with the public in order to prevent the pollution of the banks of the reservoirs and to avoid the fires with the destruction of forests, creation of places of recreation in the forest lawns, creation of additional workplaces).The economic security of forest enterprises depends to a large extent on the effectiveness of farm management, which should ensure the development and implementation of measures aimed at the sustainable development of forestry, as the main source of cash receipts is the sale of harvested timber. The ecological safety of forestry is under the influence of a large number of environmental factors, which, in most cases, is the cause of environmental problems. Thus, ecological safety of forest enterprises should be based on the consideration of the natural functions of the forest areas of the enterprise – landscapes, protection of natural ecosystems (increasing forest cover, conservation of biodiversity, etc.).Thus, in our opinion, the main feature of socioecological and economic safety of forestry is the integration of the principles of social, ecological and economic management, namely: the introduction of an ecosystem approach to forestry practices and the development of technological, organizational, economic, and institutional and regulatory programs that will provide a sustainable, ecologically balanced and socially responsible, multipurpose use and reproduction of forest resources; development and approval of criteria for balanced development of forestry; conducting ecological certification of forests; implementation of the system of comprehensive user responsibility for the condition of the forests; support of forestry through introduction of market and state regulation mechanisms; introduction of economic and legal mechanisms that stimulate the expanded reproduction of forest resources and increase the forest cover of the country; implementation of ecological and economic planning of forestry; ensuring the reproduction of forest and natural vegetation cover using technologies that contribute to the conservation and development of biodiversity; transition to selective ways of cutting; forestry modernization through the use of ecologically safe and modern logging technologies, etc.Socioecological and economic security is interpreted as a complex system of balancing the interests of «nature – man–enterprise», which presupposes the state of the enterprise's security from internal and external threats, in which there is the necessary resources and other possibilities for maintaining this function in the long-term and whose production activity does not lead to the emergence environmental or social dangers aimed at preserving natural ecosystems and building up scientifically grounded resource potential through the implementation of programs ozshyrenoho reproduce and ensure the principles of social responsibility and compliance with social standards.
Keywords: social security, economic safety, ecological safety, socioecological and economic safety.